PEMBERDAYAAN MASYARAKAT HIDUP BERSIH DAN SEHAT SEBAGAI UPAYA PENINGKATAN KUALITAS LINGKUNGAN DAN KESEHATAN - Azteria, Veza; Veronika, Erna; Rosya, Ernalinda; Irfandi, Ahmad (LPPM Institut Pendidikan Nusantara Global, 2024)
To improve environmental health in society, it is necessary to implement clean and healthy living behavior to achieve a better standard of living. One strategy that can be used to achieve this level of public health is to provide understanding and education towards public awareness in implementing a clean and healthy lifestyle starting from the family, school, and broader community levels. Community empowerment is an essential part of health promotion and is the spearhead for it. Empowerment will be more successful if carried out through partnerships and using appropriate methods and techniques. Community service activities have been in the RW 07 Tegal Alur 1 Cengkareng area, West Jakarta, for three months, from June to August 2023. This activity is carried out using methods that are adapted to the environmental conditions of the RW 07 Tegal Alur 1 Cengkareng community, namely by conducting counseling and questions and answers. With residents facilitated by the Tegal Ali Community Health Center 1. Education by distributing door-to-door posters regarding local environmental management. Conduct FGD using a light discussion method with several RW 07 residents regarding PHBS issues and health problems faced by RW 07 residents. The target group for this activity is all households in the RW 07 Tegal Alur 1 Cengkareng West Jakarta area, with a minimum of 30 people. The target or partners also involved the Tegal Alur 1 Community Health Center as a research assistant in educating residents. Based on the results of this counseling, it was found that there was an increase in knowledge of 2.129% and an increase in people's attitudes of 0.097% in implementing clean and healthy living behavior. This routine outreach can improve public health, especially in increasing knowledge and awareness of the importance of PHBS behavior to enhance environmental quality and public health.